Development of an IoT-Enabled In-situ Soil Monitoring System for Enhancing Precision in Agricultural Practices - , Jelili Aremu Oyedokun, Muniru Olajide Okelola, Elijah Olusayo Omidiora, Wasiu Babatunde Akanbi, Olusayo Adekunle Ajeigbe (Archives of Current Research International, 2025)
The increasing global demand for food production necessitates the adoption of advanced technologies to optimize agricultural practices. This paper focuses on the development of an Internet of Things (IoT)-enabled in-situ soil monitoring system designed to enhance precision agriculture. The system includes a network of high-tech soil sensors that can measure important soil parameters like moisture, temperature, pH, electrical conductivity (EC), and levels of key nutrients (nitrogen, phosphorus, and potassium). These parameters are continuously monitored in real-time and transmitted to a cloud-based platform for secure data storage. The system provides farmers with actionable insights into soil health and nutrient status, enabling data-driven decision-making for efficient irrigation, fertilization, and crop management. By leveraging IoT technology, this approach enhances resource utilization, improves agricultural productivity, and promotes sustainable farming practices. The implementation of this system has the potential to optimize crop yields while minimizing environmental impact, contributing to the advancement of smart agriculture and global food security.